Urban Protection And Renewal Dilemma: İzmir Mezarlıkbaşı - Akpınar, Figen; Toköz, Özge Deniz; Turan, Mine; Hamamcıoğlu Turan, Mine; Toköz, Özge Deniz; Akpınar, Figen (İstanbul Teknik Üniversitesi, 2021)
At the beginning of the 21st century, efforts to preserve cultural heritage in historical settlements is a highly problematic and multi-faceted issue in Turkey. Al-though conservation legislation dates back to 60 years ago, heritage conservation has not been internalized and accepted in the wider part of society, and, has not established a sound political foundation. On the other, however, there is also a lack of integrated land-use planning and management. The purpose of this study is to present the difficulties of dealing with the conservation, renewal, and regeneration for heritage areas in the historic core of İzmir, Mezarlıkbaşı-Kemeraltı, as well as to discuss the intrinsic physical qualities, dynamic characters and diversity of community groups with a view of new spatial agenda. The objective of the study is therefore twofold: 1) documentation of the physical characteristics and values for understanding the place; 2) to evaluate incorporating integrated strategic planning and management approach pointing the need for incorporating, leadership, partnership, integration and inclusion as a policy guideline for the safeguarding the heritage area. Our findings show that the Municipality of İzmir has made a significant attempt as TARKEM’s leadership position, which has succeeded in attracting national and international interest in Kemeraltı and creating opportunities for the future, but partnership (operation), management (structure) and inclusion (its processes) still lack. Community groups are not seen as part of the planning activities and planning has been remote, fragmented and exclusively missing an integrated planning management approach. © 2021, Istanbul Teknik Universitesi, Faculty of Architecture. All rights reserved.
Keywords: Cultural heritage; Conservation planning and legislation; Safeguarding cultural heritage